Upaya Pemeliharaan Kesehatan dan Kebersihan di Pondok Puteri Pusat Pesantren Zainul Hasan Genggong Berdasarkan Ajaran Al-Qur'an dan Hadits - Nurul Khofifah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore and analyze the implementation of health and cleanliness at Pondok Pesantren Zainul Hasan Genggong based on the guidance of the Qur'an and Hadith. The research employed interviews, observations, and dokumentation as its methods.The results of interviews with the pesantren's caregivers, senior students, and cleaning staff indicated that cleanliness and health are integral parts of the character education provided at the pesantren. Islamic teachings on cleanliness, as stated in the Qur'an and Hadith, are applied in various aspects of student life, from personal hygiene practices such as ablution and bathing to the cleanliness of the pesantren environment. Observations revealed that public facilities such as bathrooms, dining rooms, and ablution areas are consistently maintained, with each student responsible for keeping their room and surrounding areas clean. Documentation obtained shows the existence of written policies on cleanliness and health, as well as regular health check-ups for the students. The implementation of cleanliness and health has a positive impact on the physical and mental well-being of the students, as well as fostering discipline and environmental awareness. This study also identified challenges such as limited facilities and the need to raise awareness about cleanliness among some students. Overall, Pondok Pesantren Zainul Hasan Genggong successfully implements Islamic teachings on cleanliness and health, positively affecting the well-being of its students.